Influence of medical humanization on patients’ attribution in negative medical situations with communication as the mediator: a questionnaire study - Wang, Peijuan; Wang, Yao; Wu, Qing; Su, Fan; Chang, Xin (Frontiers in Public Health, 2023)
Background Patients’ attribution in negative medical situations plays a vital role in reducing medical conflicts and developing high-quality healthcare. The purpose of this study was to investigate the triadic relations among patients’ attribution, medical humanization and communication. Furthermore, the mediating effect of communication was tested. Methods A cross-sectional study on the relationship between patients’ attribution in negative medical situations and medical staff’s humanization and communication was conducted, with 3,000 participants totally from 103 hospitals of three different levels in different regions. Results There were significant positive correlations among medical staff’s humanization, communication and patients’ attributional styles (r = 0.112–0.236, p < 0.001 for all). Medical humanization had direct predictive effects on patients’ attributional style in negative medical situations (β = 0.14, p < 0.01). Mediation analysis also indicated the indirect predictive effect of medical humanization on patients’ attributions through communication (β = 0.02, p < 0.01). Conclusion Patients’ attribution in negative medical situations is predicted by patients’ perception of medical staff’s humanization in healthcare and physicians’ communication skills. Medical humanization not only affects patients’ attributions in negative situations directly, but also influences patients’ attributions via communication indirectly. The humanistic care should be included in medical education for healthcare professionals, and professional training on medical staff’s humanization and communication skills is strongly needed to establish healthy and harmonious doctor–patient relationship.